Dynamic blend of ethnoscience and inquiry in a digital learning platform (e-learning) for empowering future science educators' critical thinking - Prayogi, Saiful; Ahzan, Sukainil; Indriaturrahmi; Rokhmat, Joni; Verawati, Ni Nyoman Sri Putu (Journal of Education and e-Learning Research, 2023)
Inquiry-based learning overcomes the gap between the acquisition of knowledge through discovery though it is not always directly proportional to students' development of critical thinking (CT). Knowledge about the real-world contexts in which children will learn is the first step in cultivating CT in science learning. Science inquiry is most relevant when it is linked to the cultural context and local wisdom in which students are growing and developing. On one hand, the current focus of learning is on digital systems which can also provide opportunities to enhance CT. The current study aims to implement a blend of inquiry-based learning and Ethnoscience on a digital learning platform (e-learning) and assess its effect on the pre-service science teachers’ (PSTs) CT abilities. The study is conducted using an experimental method involving PSTs as participants. Several valid test instruments are employed to measure CT skills and the results are analyzed. According to the study's findings, there have been notable advancements in CT due to the digital learning platform's dynamic fusion of Ethnoscience and inquiry. This study demonstrates that the dynamic blend of Ethnoscience and inquiry in a digital learning platform can serve as a cutting-edge learning method for empowering CT particularly in future science teachers.